2022
DOI: 10.3892/etm.2022.11424
|View full text |Cite
|
Sign up to set email alerts
|

COVID‑19‑related psychiatric manifestations requiring hospitalization: Analysis in older vs. younger patients

Abstract: The complex manifestations of COVID-19 include psychiatric symptoms, having multifaceted profiles with varying severity during the acute phase and further during the recovery period. Limited data exist which have analyzed whether there are any age-related differences. A study lot of 89 COVID-19 patients with mild-to-moderate SARS-CoV-2 infection requiring hospitalization for mental issues provided comparative data from two age groups below and above 60 years. The majority of patients had new onset of a mental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…It indicated that younger patients with COVID-19 frequently presented with delirium, bizarre behavior, and hallucinations compared to older adults. They also showed that these young adults are more likely to be diagnosed and fully recover; the onset is often abrupt, may last for weeks or months, or maybe as short-lived as a few hours to days [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…It indicated that younger patients with COVID-19 frequently presented with delirium, bizarre behavior, and hallucinations compared to older adults. They also showed that these young adults are more likely to be diagnosed and fully recover; the onset is often abrupt, may last for weeks or months, or maybe as short-lived as a few hours to days [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although subjects suffering from COVID-19 are at increased risk of thrombosis, and we have strong evidence that subjects with HHT often suffer from medical conditions that may negatively influence the clinical course of COVID-19 (like chronic anemia, heart failure, and pulmonary AVMs), recent data suggest that, actually, HHT patients may generally present milder forms of SARS-CoV2 infection [ 70 , 71 , 72 , 73 , 74 , 75 , 76 ]. Some preliminary data show a significant decrease in inflammatory cytokines detected in the HHT population—with differences lower than 50% for some cytokines like interleukines (ILs: IL-6, IL-1β, and IL12p40) and around 50% for Chemokine (C-C motif) ligand 20 (CCL20), Thrombospondin-1 (TSP-1), and Activin A [ 70 , 71 , 72 , 73 , 74 , 75 , 76 ]. If confirmed by larger studies, these HHT characteristics may explain some sort of protection against developing severe forms of COVID-19 [ 70 , 71 , 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering SARS-CoV-2 infection also affects sleep, we conducted an additional analysis on sleep disturbances among older COVID-19 patients, including sleep problems ( Karaogullarindan et al, 2021 ; Sârbu et al, 2022 ; Yadav, Yadav, Kumar, & Kumar, 2021 ) and insomnia symptoms ( Aly & Saber, 2021 ; Izquierdo-Condoy et al, 2022 ; L. Li et al, 2021 ; Nejad, Allahyari, Hosseinzadeh, Heiat, & Ranjbar, 2021 ; Rego de Figueiredo et al, 2023 ) were included. The number of references reporting the age groups and sex groups for sleep disturbances was less than one, except sleep problems using self-constructed items (age groups ( Collinge & Bath, 2023 ; Perelman et al, 2022 ) and sex groups ( Gustavsson & Beckman, 2020 ; Ikeda et al, 2022 )).…”
Section: Methodsmentioning
confidence: 99%